Multispecies probiotic administration reduces emotional salience and improves mood in subjects with moderate depression: a randomised, double-blind, placebo-controlled study - Baião, Rita; Capitão, Liliana P.; Higgins, Cameron; Browning, Michael; Harmer, Catherine J.; Burnet, Philip W. J. (Psychological medicine, 2023)
The potential antidepressant properties of probiotics have been suggested, but their influence on the emotional processes that may underlie this effect is unclear. Depressed volunteers ( = 71) were recruited into a randomised double-blind, placebo-controlled study to explore the effects of a daily, 4-week intake of a multispecies probiotic or placebo on emotional processing and cognition. Mood, anxiety, positive and negative affect, sleep, salivary cortisol and serum C-reactive peptide (CRP) were assessed before and after supplementation. Compared with placebo, probiotic intake increased accuracy at identifying faces expressing all emotions (+12%, < 0.05, total = 51) and vigilance to neutral faces (mean difference between groups = 12.28 ms ± 6.1, < 0.05, total = 51). Probiotic supplementation also reduced reward learning (-9%, < 0.05, total = 51), and interference word recall on the auditory verbal learning task (-18%, < 0.05, total = 50), but did not affect other aspects of cognitive performance. Although actigraphy revealed a significant group × night-time activity interaction, follow up analysis was not significant ( = 0.094). Supplementation did not alter salivary cortisol or circulating CRP concentrations. Probiotic intake significantly reduced (-50% from baseline, < 0.05, = 35) depression scores on the Patient Health Questionnaire-9, but these did not correlate with the changes in emotional processing. The impartiality to positive and negative emotional stimuli or reward after probiotic supplementation have not been observed with conventional antidepressant therapies. Further studies are required to elucidate the significance of these changes with regard to the mood-improving action of the current probiotic.